2017
DOI: 10.1002/2017ja024089
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parameterized small‐scale gravity waves on the migrating diurnal tide in Earth's thermosphere

Abstract: Effects of subgrid‐scale gravity waves (GWs) on the diurnal migrating tides are investigated from the mesosphere to the upper thermosphere for September equinox conditions, using a general circulation model coupled with the extended spectral nonlinear GW parameterization of Yiğit et al. (). Simulations with GW effects cut off above the turbopause and included in the entire thermosphere have been conducted. GWs appreciably impact the mean circulation and cool the thermosphere down by up to 12–18%. GWs significa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 93 publications
2
66
1
Order By: Relevance
“…Due to the excitation process, tides have periods of 1 solar day (24 h) and its harmonics, like 12 or 8 h. The tidal propagation can be either Sun-synchronous or not, and accordingly tides are called migrating or non-migrating tides (Forbes, 1995). They modulate the background wind field together with planetary waves and therefore have an impact on the propagation conditions for gravity waves (e.g., Eckermann and Marks, 1996;Senf and Achatz, 2011;Yigit and Medvedev, 2017). Upwardpropagating GW transport energy and momentum and deposit them during their breaking and filtering to the mean background flow (Holton and Alexander, 2000;Fritts and Alexander, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the excitation process, tides have periods of 1 solar day (24 h) and its harmonics, like 12 or 8 h. The tidal propagation can be either Sun-synchronous or not, and accordingly tides are called migrating or non-migrating tides (Forbes, 1995). They modulate the background wind field together with planetary waves and therefore have an impact on the propagation conditions for gravity waves (e.g., Eckermann and Marks, 1996;Senf and Achatz, 2011;Yigit and Medvedev, 2017). Upwardpropagating GW transport energy and momentum and deposit them during their breaking and filtering to the mean background flow (Holton and Alexander, 2000;Fritts and Alexander, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additional data are required for validation and more observational data are nec-essary for improving these parametrizations (Geller et al, 2013). There are approaches of gravity wave parametrization schemes, which improve the structure and magnitude of tides, but a validation with observational data is still rare (Yigit et al, 2008;Yigit and Medvedev, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their characteristics, these GWs may play important roles in both neutral thermosphere and plasma processes. For example, horizontal acceleration caused by GW momentum flux divergence from GW dissipation can result in substantial local forcing in the thermosphere, which significantly changes the neutral wind there (e.g., Vadas & Liu, ; Vadas & Nicolls, ; Vadas et al, ; Yigit & Medvedev, ). In addition, GWs capable of propagating to the bottom side of the F region (∼150–300 km) may provide the seeds for the generation of equatorial spread F plasma bubbles (e.g., Huang & Kelley, ; Huang et al, ; Hysell et al, ; Sekar & Kelley, ; Sekar et al, ; Taylor et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GWs can also induce planetary waves and tides in the T/I (e.g., Laštovička, 2006;Hoffmann et al, 2012, and references therein). Recently, Yigit and Medvedev (2017) showed that GWs can influence the migrating diurnal tide in the T/I. Although many advances have been achieved by recent studies focusing on vertical coupling by GWs between the middle atmosphere and the T/I, the mechanism of this coupling is not fully understood and open issues remain (e.g., see the review of Medvedev, 2015, 2016;.…”
Section: Q T Trinh Et Al: Satellite Observations Of Vertical Couplmentioning
confidence: 99%